152k views
2 votes
-7x + y = -19
-2x + 3y = -19

2 Answers

6 votes

Answer:

(2,-5)

Explanation:

-3(-7+y)=(-19)-3

-2x+3y=-19

21x-3y=57

-2x+3y=-19

19x=38

x=2

-7(2)+y=-19

14+y=-19

y=-5

User Savena
by
5.9k points
1 vote

Answer:

(x, y) = (2, -5)

Explanation:

Subtract 3 times the first equation from the second:

(-2x +3y) -3(-7x +y) = (-19) -3(-19)

19x = 38 . . . simplify

x = 2 . . . . . . divide by 19

Substituting into the first equation, we have ...

-7(2) +y = -19

y = -5 . . . . . . . . add 14

The solution is (x, y) = (2, -5).

-7x + y = -19 -2x + 3y = -19-example-1
User Terrill
by
5.1k points